Effect of Cryopreservation in Serum-Free and Serum-Enriched Cryoprotective Media on Formation of J-Aggregates in Rat Adrenal Cortex Cells - Yurchuk, T. A.; Bozhok, G. A.; Borovoy, I. A.; Zubov, P. M.; Gurina, T. M.; Bondarenko, T. P.; Malyukin, Yu. V. (Problems of Cryobiology and Cryomedicine, 2011)
One of necessary conditions to perform steroidogenesis by adrenal cortex cells (ACC) is the presence of the potential on mitochondrial membrane (Î”Ïˆm). To assess it the cationic dye JC-1 capable of forming j-aggregates in mitochondrion with the presence of a potential on its membrane is frequently used. In this research we estimated this ability in rat ACC after freeze-thawing in serum-free and serum-enriched cryoprotective media in DMSO concentration row. It has been established that the number of ACC containing j-aggregates increased after freeze-thawing in all cryoprotective media. This effect was kept after short-term culturing during 24 hrs only in ACC, frozen-thawed in serum-free cryoprotective media and was the most manifested in the media with 5 and 7% DMSO. Adrenal cortex cells cryopreserved in serum-enriched media did not differ from native cells by the number of cells with j-aggregates.